Evaluasi Kinerja Simpang Bersinyal Jalan Kaharuddin Nasution – Jalan Pasir Putih Kota Pekanbaru - Arianda, Meta; Trisep Haris, Virgo; Lubis, Fadrizal (JURNAL TEKNIK, 2024)
Pekanbaru is the capital of Riau Province which is the center of government activities, trade and transportation activities. The population of Pekanbaru city in 2022 will reach 1,107,327 people. So vehicle movements during peak hours often cause traffic jams. One of the roads that has high mobility in the city Pekanbaru is the Kaharuddin Nasution intersection, or better known as the Pasir Putih intersection. This intersection is a signalized intersection, at the time of the initial observation in the field the vehicles that were netted by traffic lights could not miss the queue of vehicles, this condition caused congestion for vehicles coming and going to cross the intersection. The research objective is to evaluate the performance of the Kaharuddin Nasution road intersection. The method used refers to the 2014 Indonesian Capacity Guidelines (PKJI). The results obtained that the maximum traffic volume on Monday 08 May 2023 at 17.00-18.00 was 7667 vehicles, the intersection capacity obtained was South Approach 845 Skr/hour, B Approach 275 Skr/hour, U Approach 843 Skr/hour and T Approach 761 Skr/jam. The capacity of the Kaharuddin Nasution intersection is not sufficient, because the average DJ value is 0.87 > 0.85, the average queue length (QL) is 89.72 m, the average delay is 112.79 Skr/hour. The conclusion obtained is that the level of service at the Kaharuddin Nastuion intersection is in category E (Poor). Suggestions need to be made to widen the road and rearrange the timing of traffic phases.